2011
DOI: 10.1074/jbc.m110.188524
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis and pH Control by Membrane-associated Carbonic Anhydrase IX in MDA-MB-231 Breast Cancer Cells

Abstract: Carbonic anhydrase IX (CAIX) is a membrane-bound, tumorrelated enzyme whose expression is often considered a marker for hypoxia, an indicator of poor prognosis in the majority of cancer patients, and is associated with acidification of the tumor microenvironment. Here, we describe for the first time the catalytic properties of native CAIX in MDA-MB-231 breast cancer cells that exhibit hypoxia-inducible CAIX expression. Using 18 O exchange measured by membrane inlet mass spectrometry, we determined catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 48 publications
8
84
0
Order By: Relevance
“…In contrast, Tyr449 phosphorylation was shown to occur in kidney cancer cells and was linked to downstream activation of the PI3K/Akt pathway (18). However, this phenomenon was not reproduced in breast cancer cells (9), indicating that it is cell-type specific. Moreover, information on the pertinent kinase and whether phosphorylation of Tyr449 affects CA IX function is still missing.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast, Tyr449 phosphorylation was shown to occur in kidney cancer cells and was linked to downstream activation of the PI3K/Akt pathway (18). However, this phenomenon was not reproduced in breast cancer cells (9), indicating that it is cell-type specific. Moreover, information on the pertinent kinase and whether phosphorylation of Tyr449 affects CA IX function is still missing.…”
Section: Discussionmentioning
confidence: 70%
“…24; and this work). (vi) Hypoxia increases the catalytic activity of CA IX and its ability to acidify pHe (7,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) it is located on the surface of cells [21,22]; (3) CAIXknockout mice show only a mild phenotype related to gastric pit cell hyperplasia and glandular atrophy [23]; and (4) its overexpression in cancers confers a survival advantage in hypoxia and facilitates cell migration and metastasis [16,[24][25][26]. Depletion of CAIX in cancer cell lines has been shown to result in attenuated growth of tumour xenografts and inhibition of spontaneous metastasis formation [16,26].…”
Section: Introductionmentioning
confidence: 98%
“…Microelectrode and non-invasive measurements of tumour pH have revealed that human tumours have acidic extracellular pH (pH e ), but the intracellular pH (pH i ) remains neutral to alkali 24,25 . CA IX has been shown to be a key contributor to the acidification process in tumours with the use of membrane ghost preparations 26 and tumour cell lines in which CA IX activity was either silenced or overexpressed 27 . Tumour acidification is positively correlated with enhance proliferation, invasiveness and metastasis 27,28 .…”
Section: Research Articlementioning
confidence: 99%